Risk management system in DHL - Kahindo, Winny Vyambwera (“KROK” University, 2021)
DHL Express has been the world leader in international express transport for 50 years. With an unrivaled portfolio of logistics services, DHL continues to innovate and set standards in the international logistics industry and position itself as "the logistics company for the world". Nowadays, many companies operate in a global environment; they try to do their utmost to deal with a wide range of leading and reputable suppliers, both in developed and developing countries. A DHL business is part of a complex supply chain. Global supply chains are referred to as a source of competitive advantage over other market players (Manuj and Mentzer 2008 AT). The existence of the company in the global environment provides access to labor, components and raw materials, increased opportunities to increase profitability, a better share of product markets, arbitrage opportunities and additional incentives, which may be offered by host governments to attract foreign capital Supply Chain Management is a very complex set of operations and functions with a wide range of inherent risks.